2022
DOI: 10.3390/biomedicines10050987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D on Graft-versus-Host Disease

Abstract: The different cell subsets of the immune system express the vitamin D receptor (VDR). Through the VDR, vitamin D exerts different functions that influence immune responses, as previously shown in different preclinical models. Based on this background, retrospective studies explored the impacts of vitamin D levels on the outcomes of patients undergoing allogeneic hematopoietic stem-cell transplantation, showing that vitamin D deficiency is related to an increased risk of complications, especially graft-versus-h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 190 publications
0
7
0
Order By: Relevance
“…Despite conflicting results, pediatric studies often report that VDD is not associated with aGVHD, rather related with cGVHD and low survival rates 3,4,18 a statement with which the findings of this study conflict: where only one patient died (Table 1) and no association was found with cGVHD. One plausible explanation for this difference can be that all other studies 3,6,8,12,17 included patients with various malignant and non‐malignant conditions with different baseline problems such as leukemias and immunodeficiencies prior to HSCT.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Despite conflicting results, pediatric studies often report that VDD is not associated with aGVHD, rather related with cGVHD and low survival rates 3,4,18 a statement with which the findings of this study conflict: where only one patient died (Table 1) and no association was found with cGVHD. One plausible explanation for this difference can be that all other studies 3,6,8,12,17 included patients with various malignant and non‐malignant conditions with different baseline problems such as leukemias and immunodeficiencies prior to HSCT.…”
Section: Discussionmentioning
confidence: 67%
“…As all our patients received vitamin D supplementation and the fact that low vitamin D 3 of the patients improved in the 3rd month after HSCT supports that vitamin D supplementation may have protective effect against cGVHD. Furthermore, in HSCTs with peripheral blood stem cell (PBSC) sources in patients with VDD, we observed aGVHD more frequently than in HSCTs with other sources which may possibly be explained by the absence of antiproliferative effect of vitamin D 3 on peripheral blood lymphocytes 3,22,23 in the early stages after HSCT. The reason why this association was not observed in other studies needs to be investigated comprehensively if this issue is only related with TM patients who have additional hormonal problems described above.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations